Mobilisation of enterocyte fat stores by oral glucose in humans. - Robertson, MD; Parkes, M; Warren, B; Ferguson, D; Jackson, K; Jewell, D; Frayn, K (2003)
BACKGROUND AND AIMS: When a high fat oral load is followed several hours later by further ingestion of nutrients, there is an early postprandial peak in plasma triacylglycerol (TG). The aim of this study was to investigate the location and release of lipid from within the gastrointestinal tract. METHODS: Ten healthy patients undergoing oesopho-gastro-duodenoscopy (OGD) were recruited. At t=0, all patients consumed a 50 g fat emulsion and at t=5 hours they consumed either water or a 38 g glucose solution. OGD was performed at t=6 hours and jejunal biopsy samples were evaluated for fat storage. A subgroup of five subjects then underwent a parallel metabolic study in which postprandial lipid and hormone measurements were taken during an identical two meal protocol. RESULTS: Following oral fat at t=0, samples from patients that had subsequently ingested glucose exhibited significantly less staining for lipid within the mucosa and submucosa of the jejunum than was evident in patients that had consumed only water (p=0.028). There was also less lipid storage within the cytoplasm of enterocytes (p=0.005) following oral glucose. During the metabolic study, oral glucose consumed five hours after oral fat resulted in a postprandial peak in plasma TG, chylomicron-TG, and apolipoprotein B48 concentration compared with oral water. CONCLUSION: After a fat load, fat is retained within the jejunal tissue and released into plasma following glucose ingestion, resulting in a peak in chylomicron-TG which has been implicated in the pathogenesis of atherosclerosis.